The unattainable logic of treaty antinomy - Zapatero, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The general rules on treaty conflict exhibit limitations in promoting international legal consistency. These relate to their incompleteness, reliance on subject-matter distinctions, inapplicability to third parties, and—crucially—the absence of formal and dynamic mechanisms for derogating or annulling conflicting provisions. Such shortcomings are aggravated by the increasing institutionalization and specialization of international law, alongside the lack of effective general organs or procedures capable of addressing conflicts across multiple special regimes. As a result, a strong presumption against the very existence of treaty conflict has become entrenched.